2010
DOI: 10.1002/ange.201000003
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Synthesis of Functionalized Conjugated Enynes: Palladium‐Catalyzed Bromoalkynylation of Alkynes

Abstract: Von der gleichen Seite: Die direkte cis‐Addition von Bromalkinen 1 an Alkine 2 in Gegenwart eines Palladium(II)‐Katalysators ergibt difunktionalisierte Enine 3 als Produkte. Die Methode bietet einen einfachen Zugang zu Bromalkeninen. Ein ungewöhnlicher Reaktionsmechanismus wird vorgeschlagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…[4] Thus, we decided to react phenylethynyl bromide (2 a) with norbornene (1 a), expecting to obtain 2-bromo-3-(2-phenylethynyl)bicyclo[2.2.1]heptane (3 aa; Scheme 1). However, when using the previously optimized conditions, [2] we did not detect the formation of 3 aa, instead we obtained 2-bromo-7-(2-phenylethynyl)-bicyclo[2.2.1]heptane (3 a) in excellent yield, as confirmed by 1 H NMR spectroscopy. This unexpected result attracted our interest, since, to the best of our knowledge, no example of a direct 7-alkynyl bromonorbornane formation has been reported.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…[4] Thus, we decided to react phenylethynyl bromide (2 a) with norbornene (1 a), expecting to obtain 2-bromo-3-(2-phenylethynyl)bicyclo[2.2.1]heptane (3 aa; Scheme 1). However, when using the previously optimized conditions, [2] we did not detect the formation of 3 aa, instead we obtained 2-bromo-7-(2-phenylethynyl)-bicyclo[2.2.1]heptane (3 a) in excellent yield, as confirmed by 1 H NMR spectroscopy. This unexpected result attracted our interest, since, to the best of our knowledge, no example of a direct 7-alkynyl bromonorbornane formation has been reported.…”
supporting
confidence: 54%
“…[1] We previously achieved highly regio-and stereoselective bromoalkynylation of internal alkynes for the synthesis of conjugated cis-bromoalkenynes. [2] Subsequent research on this subject revealed a further use of bromoalkynes in complex molecule synthesis.…”
mentioning
confidence: 99%
“…We next tested the reaction in the presence of different catalysts. PdA C H T U N G T R E N N U N G (PPh 3 ) 2 Cl 2 , was superior to any other palladium catalysts so far tested (entries 5,[10][11][12][13][14][15][16][17]. Notably, the reaction was not effective when only PdA C H T U N G T R E N N U N G (OAc) 2 or PdA C H T U N G T R E N N U N G (CH 3 CN) 2 Cl 2 was employed (entries 10 and 11).…”
mentioning
confidence: 90%
“…metaChloroaniline 2i afforded the para-cyclization regioisomer 4i and ortho-cyclization isomer 5i in 30% and 27% yields (entry 9). On the other hand, different combinations of substituents on the alkyne and alkene of bromoenynes can be used to allow the synthesis of alkyl-and arylsubstituted quinolines (entries [10][11][12][13]. When alkyl substituents were on the end of alkyne, the desired product could not be observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation